1993
DOI: 10.1089/jir.1993.13.267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrates on the Pharmacokinetics of Human Interferon-γ

Abstract: Human interferon-gamma (IFN-gamma) has two N-linked glycosylation sites at positions 25 and 97 of the 143-amino-acid-long secretory form. To study the role of glycan residues in the pharmacokinetics of IFN-gamma, we produced recombinant IFN-gamma molecules lacking either one or both of the glycosylation sites (Asn mutated to Gln) by baculovirus expression in insect cells. In addition, we produced the fully glycosylated forms both in insect cells and in human leukocyte cultures. Two million units of each IFN we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…Thus, an engineered N-glycosylated scFv containing high-mannose carbohydrate chains at a C-terminal extension was more rapidly cleared from circulation than the unmodified scFv (32). Similar observations were made for interferon-␥ (29). We found that the three N-glycosylated scDb variants all contained N-glycans of the complex type (bi-, tri-, and tetra-antennary).…”
Section: Discussionsupporting
confidence: 76%
“…Thus, an engineered N-glycosylated scFv containing high-mannose carbohydrate chains at a C-terminal extension was more rapidly cleared from circulation than the unmodified scFv (32). Similar observations were made for interferon-␥ (29). We found that the three N-glycosylated scDb variants all contained N-glycans of the complex type (bi-, tri-, and tetra-antennary).…”
Section: Discussionsupporting
confidence: 76%
“…Kanda et al (2007) also demonstrated faster clearance in the b-phase of an anti-CD 20 antibody with Man5 glycans after intravenous injection of 20 mg antibody per mouse. Although a 1.5-to 3-fold lower half-life in serum was observed for oligomannose containing antibodies compared to the control antibody in these studies, the 4.6-day (Kanda et al, 2007) and 2.8-to 4-day (Wright et al, 1994(Wright et al, , 1998 half-lives of the oligomannose containing antibodies are still much longer than many non-antibody like glycoproteins with oligomannose residues, which have half-lives of a few minutes (Kogerlberg et al, 2007;Sareneva et al, 1993;Van Patten et al, 2007). The difference in half-lives between antibody and nonantibody like glycoprotein with oligomannose residues prompted us to compare their binding to mannose receptor (Jones et al, 2007;Su et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
“…Tunicamycin treatment resulted in a 4-5-fold decrease in the level of synthesized IFN-y protein, and the amount of secreted protein was about 30% of the (Fig. 3 B), is probably due to the C-terminal protein processing found earlier by us and others both in natural and recombinant IFN-y [8,[25][26][27].…”
Section: Role Of N-glycosylation In the Synthesis And Secretion Of Ifmentioning
confidence: 58%